The Effects of Nicorandil and Nifekalant, Which Were Injected into the Pericardial Space, for Transmural Dispersion of Repolarization in the Pig - Hiroyuki Ito, MD; Taku Asano, MD; Youichi Kobayashi, MD; Tatsuya Onuki, MD; Fumito Miyoshi, MD; Taka-aki Matsuyama, MD; Yoshino Minoura, MD; Norikazu Watanabe, MD; Mitsuharu Kawamura, MD; Kaoru Tanno, MD; Takashi Katagiri, MD (Journal of Arrhythmia, 2007)
Introduction: Some studies have reported that transmural dispersion of repolarization (TDR) is involved in the onset of ventricular arrhythmia. We investigated the effects of nicorandil (NIC) and nifekalant (NIF) injected into the pericardial space, on TDR and T waves in the pig. Methods and Results: We injected NIC 4 or 8 mg and NIF 50 or 100 mg at intervals into the pericardial space for eleven pigs. The effects of these drugs were investigated on the effective refractory period (ERP) between the endocardial and epicardial myocardial cells, as well as on QT time, QT peak-end (QTcpe) as an index of TDR, and T waveforms, respectively. QTcpe increased from 91 ± 21 to 116 ± 19 msec, 2.8 min after injection of NIC (p < 0.01), although corrected QT (QTc) interval did not changed. But 5.5 min after injection, QTc decreased while QTcpe recovered. T wave amplitude significantly increased, and epicardium ERP decreased. When NIF was injected, TDR decreased from 55 ± 10 msec to 44 ± 8 msec (p < 0.01) although QTc did not change. In a later phase, QTc increased (p < 0.01) and QTcpe recovered. T wave amplitude rapidly decreased and became negative. Conclusion: Injected into the pericardial space, NIC and NIF brought about certain changes in ERP, QT and T waveform. Furthermore, NIC increased TDR while NIF decreased TDR.